Identification of the histone acetyltransferase gene family in the Artemisia annua genome - Guo, Yang; You, Yan; Chen, Furong; Liao, Yong (Frontiers in Plant Science, 2024)
As the most effective therapeutic drug for malaria, artemisinin can only be extracted from Artemisia annua L., which is sensitive to the surrounding growing habitat. Histone acetyltransferases (HATs) contain acetyl groups, which modulate mRNA transcription and thereby regulate plant environmental adaptation. Comprehensive analyses of HATs have been performed in many plants, but systematic identification of HATs in medicinal plants is lacking. In the present study, we identified 11 AaHATs and characterized these genes into four classes according to their conserved protein structures. According to the phylogenetic analysis results, potential functions of HAT genes from Arabidopsis thaliana, Oryza sativa and A. annua were found. According to our results, AaHAT has a highly conserved evolutionary history and is rich in highly variable regions; thus, AaHAT has become a comparatively ideal object of medical plant identification and systematic study. Moreover, motifs commonly present in histone acetyltransferases in the A. annua genome may be associated with functional AaHATs. AaHATs appear to be related to gene-specific functions. AaHATs are regulated by cis-elements, and these genes may affect phytohormone responsiveness, adaptability to stress, and developmental growth. We performed expression analyses to determine the potential roles of AaHATs in response to three environmental stresses. Our results revealed a cluster of AaHATs that potentially plays a role in the response of plants to dynamic environments.